Konsep Siyasah dan Adab Bernegara Menurut Imam Al-Ghazali - Kholili Hasib (STAIFAS-Press, 2017)
Imam al-Ghazali is an expert scholar of various fields, kalam, tasawuf, fiqh, andphilosophy. Even so, he did not care about the political issues of his time. Hispolitical thinking is in his book Al-Tibr al-Masbuk fii Nashihat al-Muluk.According to Imam al-Ghazali, various political issues that engulf the Islamicworld boils down to a scientific crisis. Therefore, Imam al-Ghazali's criticism isdirected to the 'ulama' as the bearer of knowledge. The tyranny of science hascreated an epistemological crisis that leads to the weakness of the ummah againstforeign powers. Thus, the thought of politics is described by al-Ghazali imam withSufism frames. Efforts to improve the politics of al-Ghazali is done by applyingthe concept of amar ma'ruf nahi munkar to the ulama and the ruler at once. Stagesof business is done, warning, then advice. Al-Ghazali is very committed to thefactors of improvement and renewal. For him, a scholar or scientist should notundertake a constructive reform in the political arena. Because this is a form ofamar ma'ruf nahi munkar.Â Keyword: Siyasah Syarâ€™iyah, Adab, Epistemologi